Upaya Meningkatkan Hasil Belajar Siswa dalam Pembelajaran IPS Melalui Metode Ceramah di Kelas VI SD S Tiga Hati - Aidil Fahmi Saragih (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2022)
The main task of the teacher is to help students in terms of learning. In the process of teaching and learning teachers must provide courses to solve problems in the classroom, evaluating student learning, both before pre, middle and after class. A teacher must have high professional ability to carry out his or her role. Research has been conducted on